2020
DOI: 10.1038/s41467-020-17179-4
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol metabolism drives regulatory B cell IL-10 through provision of geranylgeranyl pyrophosphate

Abstract: Regulatory B cells restrict immune and inflammatory responses across a number of contexts. This capacity is mediated primarily through the production of IL-10. Here we demonstrate that the induction of a regulatory program in human B cells is dependent on a metabolic priming event driven by cholesterol metabolism. Synthesis of the metabolic intermediate geranylgeranyl pyrophosphate (GGPP) is required to specifically drive IL-10 production, and to attenuate Th1 responses. Furthermore, GGPP-dependent protein mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 60 publications
2
56
0
Order By: Relevance
“…It has been reported that Prdm1 promotes IL-10 expression in B cells 21 when stimulated with CpG, while Prdm1-deficient mice have more IL-10 + B cells 22 . Butyrate hinders B cell differentiation into plasmablasts 20 , in which Prdm1 plays a vital role 23 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that Prdm1 promotes IL-10 expression in B cells 21 when stimulated with CpG, while Prdm1-deficient mice have more IL-10 + B cells 22 . Butyrate hinders B cell differentiation into plasmablasts 20 , in which Prdm1 plays a vital role 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptional analyses of human activated IL-10 + B cells have found, as for mouse, the upregulation of genes coding for molecules involved in plasma cell differentiation, such as Blimp-1 and IRF4, thus confirming that human IL-10 + B cells are also capable of becoming ASCs ( 12 , 17 , 19 , 57 ). Interestingly, it has been suggested that human and mouse IL-10-producing ASCs can be differentiated directly from immature and naïve B cells ( 15 , 55 ), which is supported by the finding that Blimp-1 is already expressed in recently activated naïve B cells ( 58 , 59 ).…”
Section: The Diversification Of Breg Phenotypesmentioning
confidence: 88%
“…STAT3 phosphorylation is increased in CD40-activated transitional B cells of healthy subjects but not in those from SLE patients ( 26 ). In addition, CREB, p38 MAPK, ERK1/2, and PI3Kδ have been described to be required for IL-10 upregulation following TLR and/or CD40L stimulation ( 58 , 67 , 110 ). c-Maf, a well-known transactivator of IL-10 in various cell types, has also been shown to mediate IL-10 transcription by LPS-stimulated murine B cells ( 111 ).…”
Section: Regulation Of Il-10 Expression By B Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, protein prenylation was shown to limit hyper-production of proinflammatory cytokines as well as constitutive activation of pyrin inflammasome in macrophages [ 76 ]. The anti-inflammatory effects of protein prenylation extend to other cell subsets such as B cells by inducing their production anti-inflammatory IL-10 thus promoting anti-inflammatory regulatory B cell differentiation [ 81 ].…”
Section: Immunometabolism and Impact On Immune Cell Differentiatiomentioning
confidence: 99%